Changing leadership and rural power structure - Mozumdar, L; Ali, RN; Farid, KS; Kabir, MS (Journal of the Bangladesh Agricultural University, 2010)
The present study attempts to assess the nature of changes occurred in the leadership pattern of rural power structure in Bangladesh. A complete household survey of Sutiakhali Namapara village in Sadar Upazila of Mymensingh district was undertaken to identify rural leaders. Among 92 households, a total of 18 leaders were identified by using the positional, the reputational, and the issue participation approach. The information about the changing aspects of rural power structure and the leadership pattern were collected by formal and informal interviews, Focus Group Discussions (FGDs), participant observation, and storytelling. Findings showed that majority of the leaders were young (55.56%), had no specific lineage status (38.89%) and most of them (38.89%) were businessmen. Education, personal qualities and affiliation with major political parties were more important factors influencing rural leadership. A remarkable change occurred in the power structure of rural Bangladesh during the last decade, more specifically from 2001 to 2007. Among the elites, the younger ones were dominating the villages, whereas, the older ones were losing the elite status, because of their lack of positional status and power. It also revealed that the rural leaders changed their policy to create and sustain power, such as building business associations, forming party networks involving with different government and non-government organizations and maintaining a good link with local Member of Parliament etc. Finally, it can be said that a significant change occurred in leadership pattern and power structure of rural Bangladesh. Keywords: Power structure; Leadership; Lineage status; Personal qualities DOI: 10.3329/jbau.v6i2.4844 J. Bangladesh Agril. Univ. 6(2): 429-436, 2008